The step beyond: Les deux excès de la phénoménologie française - de Gramont, Jerome (Kwartalnik Naukowy Fides et Ratio, 2021)
Since its birth, philosophy has been dedicated to a step beyond the doxa and the natural attitude. The very name of metaphysics testifies to this constant movement of going beyond and phenomenology inherits it, which invites to a radical change of attitude. In this respect, French phenomenology is not so much in the continuity of this step beyond as it is carrying it to its extreme limits, at the risk of breaking the method invented by (German) historical phenomenology, but in the name of a fidelity to new phenomena. As different as they are, these works of French phenomenology could have in common that they take a step beyond. This contribution would like to give two examples of this ever increasing radicality with Maurice Blanchot’s phenomenology of literary experience and Jean-Luc Marion’s recent phenomenology of revelation.